Endovascular Treatment of Pulmonary Artery Pseudoaneurysms Post-COVID-19 Pneumonitis - Kundaragi, Nischal G.; K., Sunil Kumar; Talwade, Rahul; Lokeshwaran, Srivatsa; K., Priyanka V. (Journal of Clinical Interventional Radiology ISVIR, 2022)
Pulmonary artery pseudoaneurysms (PAPs) are uncommon entities consisting of contained rupture of the pulmonary artery and are a potentially fatal cause of hemoptysis. We describe two index cases of left lower lobe PAPs and arterial ectasia post-COVID-19 pneumonitis and their endovascular treatment with Amplatzer vascular plug, coils, and glue.
Keywords: COVID-19 infection; pulmonary artery pseudoaneurysm; embolization; hemoptysis